МОДЕЛЬ ЛОКАЛЬНОГО ИОННО-ЛУЧЕВОГО ОСАЖДЕНИЯ ПЛАТИНЫ СФОКУСИРОВАННЫМ ПУЧКОМ ИОНОВ - D. G. Lapin; I. S. Ovchinnikov (Российский технологический журнал, 2017)
In this paper, the problems associated with the process of local ion-beam deposition of the material from the gas phase is analyzied. It has been established that the ion-beam deposition of a material from the gas causes a redeposition effect, exposure time and the current of the primary ion beam which is significantly influence on it. The necessity of modeling the ion-beam deposition process is substantiated to for reducing the size of the area of redeposition. An analysis of existing models has shown that they do not take into account all the technological parameters influencing the process of local ion-beam deposition. The refined mathematical model for predicting the focused ion beam deposition rate of platinum from the gas phase takes into account the magnitude of the region of overlap of the primary ion beam is proposed in this paper. Investigations of simulation results have shown that the deposition rate increases with increasing of overlap area. The values of the overlap region at which the deposition process passes into the etching process is determine and the relationship characterizing the beam current and the overlap region where deposition rate has maximum is established. It is shown that when the structures are deposited at the maximum deposition rate (determined in the simulation), the size of the region of the redispersion decreases.